4x+13=7x-8

Simple and best practice solution for 4x+13=7x-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+13=7x-8 equation:


Simplifying
4x + 13 = 7x + -8

Reorder the terms:
13 + 4x = 7x + -8

Reorder the terms:
13 + 4x = -8 + 7x

Solving
13 + 4x = -8 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
13 + 4x + -7x = -8 + 7x + -7x

Combine like terms: 4x + -7x = -3x
13 + -3x = -8 + 7x + -7x

Combine like terms: 7x + -7x = 0
13 + -3x = -8 + 0
13 + -3x = -8

Add '-13' to each side of the equation.
13 + -13 + -3x = -8 + -13

Combine like terms: 13 + -13 = 0
0 + -3x = -8 + -13
-3x = -8 + -13

Combine like terms: -8 + -13 = -21
-3x = -21

Divide each side by '-3'.
x = 7

Simplifying
x = 7

See similar equations:

| (Y-9)-(y+3)=4y | | -3(2q+2)= | | (x+2)+(9x-52)=180 | | 25000+3000n=36000+2000n | | 11+4x=2(11+4x) | | 0.3-2=7 | | 3x+2(x-1)=2 | | 4x+12-3x=19 | | 4x^4-4x^3-25x^2+x+6=0 | | 5/9x-1/3=1/5 | | 18+2=44 | | 3x-3+9=5x-7-3x | | 9x+3=7x+8 | | 6p+7q=39 | | (2x+66)=(8x+6) | | 7v+10=8v+v | | m^2=-3m+18 | | -21=0.5c-11 | | 17+w=94 | | p+.3p=.6 | | x^4-2x^3+x^2-4=0 | | 2x^2+9x=6x+20 | | 0.08(3v-4)=0.4(v-4) | | 3(v+8)-10v=-7v-42 | | 4+0.6x=16 | | 20x-6=40x+6 | | -78+n=-133 | | 2x+42+1+3x-31=180 | | -6(-6+5x)-6(x-7)=x+3+7-3x | | x^3-4x^3+3x=0 | | 4r+1=11a+8 | | 3-.22222222b=.33333333b-7 |

Equations solver categories